Twilight on the South Carolina Rice Fields : Letters of the Heyward Family, 1862-1871 - Heyward, Edward Barnwell, 1826-1871 (Book collections on Project MUSE., 2010)
A firsthand account of the Civil War and Reconstruction in the Old South rice kingdom from one of South Carolina's founding families.